Governance and City Regeneration - A New Methodological Approach for Design and Evaluation - Paulo Neto; Maria Manuel Serrano (European Regional Science Association (ERSA), 2011)
Governance has become a central topic among policymakers. There is an international consensus that policymaking is evolving from a traditional top-down government approach towards a system of governing that focuses on engaging the citizens within an area (Cabus, 2003). New forms of governance targeting urban competitiveness are increasingly oriented to vertical (between lower and high levels of government and cooperation forms between entities and firms along the production chain) and horizontal (between firms or different municipalities or public and private entities) cooperation (OEDC, 2005). Urban renewal policies underwent significant changes in recent decades. Synthetically, the following periods can be distinguished: 1970s: "hard" urban renewal - extensive physical interventions; 1980s: "soft" urban renewal - efforts to keep the original population in place; 1990s: "integrated urban renewal" - combining physical, economic and social interventions (Tosics, 2010). And over the last few years there has been a gradual shift in the understanding of what should be the tools and objectives of urban regeneration policies, with a greater emphasis on process-related and `soft' issues of stakeholder engagement, partnership formation, leadership development, `institutional capacity' development, knowledge and learning (Magalh\~aes, 2004). This shift in the understanding of urban regeneration processes accomplishes the growing importance in literature of concepts like urban governance, institutional relational density, creativity, social capital, city branding and place marketing. The main purpose of this paper is to propose a new methodology for territorial analysis and planning focused on urban regeneration processes and its governance mechanisms. A new methodology that seeks, for each specific urban context, contribute to the following results: 1) Help select the most appropriate governance model to be adopted for each process of urban regeneration, 2) Monitor the partnership process and help promote the partnership guidance; 3) Support the design process and the definition of the strategic approach and projects, 4) Monitor the process of implementing the strategy and support multidimensional and multiscale evaluation of its results; 5) Evaluate the socio-economic and territorial impacts of urban regeneration processes.
Keywords: 330